Dilution effects on compensation temperature in borophene core-shell structure: Monte Carlo simulations. (August 2020) - Fadil, Z.; Mhirech, A.; Kabouchi, B.; Bahmad, L.; Benomar, W. Ousi
Abstract: In this paper, we study the magnetic properties of a diluted core-shell borophene structure. The system is composed by the mixed spins σ = ±1, 0 (in the core) and S = ±3/2, ±1/2 (in the shell). Indeed, the originality of this work is to introduce the non-magnetic atoms in the shell part of the borophene monolayer system and study their effects on the magnetic properties behavior. Firstly, the ground state phase diagrams for different parameters are reported and discussed. Numerically, we use the Monte Carlo simulations (MCS) to study the effect of the dilution concentration on the magnetizations and susceptibilities of the system. Moreover, the compensation and transition temperatures decrease when increasing the dilution concentration parameter. Furthermore, the effect of the dilution concentration on the total magnetization versus the crystal field is discussed. Finally, the effects of the dilution concentration and the temperature on the hysteresis cycles are investigated. Highlights: The magnetic properties of a diluted core-shell borophene structure using Monte Carlo simulations are studied. The ground state phase diagrams are presented and discussed. The existence of the compensation and transition temperatures for special physical parameters. The hysteresis cycles of a core-shell Borophene structure are analyzed.